Teaching and Learning Lithuanian as a Foreign Language in a Multilingual Group of Adults - Našlėnaitė Eberhardt, Vaida (Vilnius University Open Series, 2023)
This article exposes some linguodidactic issues concerning teaching Lithuanian as a foreign language. Before discussing the study of multilingual students in section 3, the following theoretical premises are examined in sections 1 and 2: intercomprehension, language and multilingual awareness, L3 acquisition, experience with CLIL. The recordings of dialogues with the multilingual students show them to be aware language learners with a very specific and diverse theoretical motivation. One informant used a very traditional and grammar-oriented method for learning several languages. The main task for the teacher was to suggest a universal common learning plan and methods for the multilingual group in order to achieve the next language proficiency level and to improve students’ missing skills in language comprehension and speaking.